PENAFSIRAN ABA K.H.M. ZEN SYUKRI : STUDI METODOLOGI TAFSIR KITAB QUT AL-QALB - Ilyas, Deddy (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
K.H.M. Zen Syukri is a famous scholar in South Sumatra. He spent time in the field of religious education, both formal and non-formal. He started from the madrassa to sue to boarding school, learning from famous priest-chaplain. His figure is recognized by other scholars from various Islamic organizations.